Landuse and Forest Type Classification Proposed for Aerial Photo-interpretation - Tomar, M. S.; Maslekar, A. R. (Indian Forester, 1973)
The paper deals with the necessity of a standard classification scheme for landuse and forest cover types and gives the proposed classification system along with important definitions. This classification system is based on the experiences of the authors while carrying out Preinvestment Survey of Forest Resources with aerial photographs in various parts of the country and is recommended for large area inventory with aerial photographs.